2014
DOI: 10.1007/s00464-014-3723-3
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma detection at colonoscopy by polypectomy in withdrawal only versus both insertion and withdrawal: a randomized controlled trial

Abstract: Clinicaltrials.gov, #NCT01025960.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
2
8
1
Order By: Relevance
“…However, no control arm was included, and the MAP (0.37) was low in that study. In two published follow‐up prospective RCTs, inspection during both insertion and withdrawal did not make a significant additional contribution to adenoma detection compared with traditional detection of polyps performed during slow withdrawal . The overall ADR and MAP did not differ significantly between the two groups in these studies, and their findings were similar to the current study.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…However, no control arm was included, and the MAP (0.37) was low in that study. In two published follow‐up prospective RCTs, inspection during both insertion and withdrawal did not make a significant additional contribution to adenoma detection compared with traditional detection of polyps performed during slow withdrawal . The overall ADR and MAP did not differ significantly between the two groups in these studies, and their findings were similar to the current study.…”
Section: Discussionsupporting
confidence: 81%
“…Sanaka et al . reported that the proportion of patients classified as high risk was significantly higher in the study arm compared with the control arm . However, we found that the proportion of patients classified as high risk was similar in both groups.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations